Optically transparent magnetic nanocomposites based on encapsulated Fe3O4 nanoparticles in a sol-gel silica network - Thomas, Senoy; Sakthikumar, D.; Joy, Pattayil Alias; Yoshida, Yasuhiko; Anantharaman, Maliemadom R. (Nanotechnology, 2006)
Composite Fe3O4-SiO2 materials were prepared by the sol-gel method with tetraethoxysilane and aqueous-based Fe3O4 ferrofluids as precursors. The monoliths obtained were crack free and showed both optical and magnetic properties. The structural properties were determined by infrared spectroscopy, x-ray diffractometry and transmission electron microscopy. Fe3O4 particles of 20 nm size lie within the pores of the matrix without any strong Si-O-Fe bonding. The well established silica network provides effective confinement to these nanoparticles. The composites were transparent in the 600-800 nm regime and the field dependent magnetization curves suggest that the composite exhibits superparamagnetic characteristics.

Synthesis of bio-compatible SPION-based aqueous ferrofluids and evaluation of radiofrequency power loss for magnetic hyperthermia - Mary, Antony P. Reena; Narayanan, T. N.; Sunny, Vijutha; Sakthikumar, D.; Yoshida, Yasuhiko; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Nanoscale Research Letters, 2010)
Bio-compatible magnetic fluids having high saturation magnetization find immense applications in various biomedical fields. Aqueous ferrofluids of superparamagnetic iron oxide nanoparticles with narrow size distribution, high shelf life and good stability is realized by controlled chemical co-precipitation process. The crystal structure is verified by X-ray diffraction technique. Particle sizes are evaluated by employing Transmission electron microscopy. Room temperature and low-temperature magnetic measurements were carried out with Superconducting Quantum Interference Device. The fluid exhibits good magnetic response even at very high dilution (6.28 mg/cc). This is an advantage for biomedical applications, since only a small amount of iron is to be metabolised by body organs. Magnetic field induced transmission measurements carried out at photon energy of diode laser (670 nm) exhibited excellent linear dichroism. Based on the structural and magnetic measurements, the power loss for the magnetic nanoparticles under study is evaluated over a range of radiofrequencies.
Keywords: Magnetic heating; Magnetic hyperthermia; Magnetic relaxation; Power loss; Superparamagnetism